P187 Not a headache clinic: giant cell arteritis fast track pathways (GCA-FTP) need not be overwhelming. (20th April 2020) - Spray, Luke; Reynolds, Gary; Houghton, Karolyn; Hargreaves, Ben; Heaney, Jonathon; Thompson, Ben; Lorenzi, Alice
Abstract: Background: False positive and negative GCA diagnoses lead to significant morbidity. GCA Fast Track Pathways (GCA-FTP) are advocated in the NHS. Concern that these become 'headache clinics', lack of access to temporal artery ultrasound (TAUS) and biopsy (TAB) are cited as barriers to provision. We present prospectively collected data from referrals to our GCA-FTP demonstrating that this has not occurred in our service. Methods: Rheumatology leads our GCA-FTP providing initial investigation, TAUS for all patients and long-term management when GCA is diagnosed. Ophthalmology is the point of access for patients with visual symptoms and, if required, TAB. Results: Referral numbers for calendar years 2014 through 2018 were 70, 97, 134, 180 & 175 respectively. TAB was requested for 29, 43, 49, 57 and 41 patients and GCA diagnosed in 29, 34, 33, 43 & 40 patients per year. In 2017-18, TAUS without biopsy supported a diagnosis of GCA in 58 and excluded it in 199. Across 2017 and 2018 we received 356 referrals: 43.5% from ophthalmology, 34.3% primary care and 11.0% medicine. 59.3% were on corticosteroids. Mean age was 71 years, 73.3% were female. GCA was diagnosed in 83 (23.3%). Mean duration of symptoms at first review was 38 ±4.4 days in GCA patients and 58 ±6.4 days in non-GCA patients. Characteristic GCA clinical features were significantly higher in the GCA group (Table 1). Non-GCA final diagnoses were ophthalmic (NIAON) (13.8%) and musculoskeletal related (12.2%). 7.0% of patients received a primary headache diagnosis. In 41.4% no cause was recorded, and patients were discharged to their GP with corticosteroids stopped. Conclusion: A GCA-FTP can be a predictable service to manage. Clinical review by an experienced doctor distinguishes many non-GCA presentations from GCA when seen promptly. Most patients with GCA will be seen by rheumatology during their disease course. Distinguishing non-GCA diagnoses at later time points is significantly more challenging and means patients are exposed unnecessarily to high dose steroid, often for many months. TAUS and TAB are useful adjuncts to diagnosis and required for use of high tariff drugs. Lack of access need not however mean deferring setting up a GCA-FTP. Disclosures: L. Spray None. G. Reynolds None. K. Houghton None. B. Hargreaves None. J. Heaney None. B. Thompson None. A. Lorenzi None.